Classroom Disruptions and Classroom Management in Learning Factory Settings at Vocational Schools - Meinokat, Pierre; Wagner, Ingo (International Journal for Research in Vocational Education and Training, 2025)
Context: As part of vocational education and training, learning factories are a new, hands-on learning setting in which students can create products with realistic digital manufacturing equipment while still in vocational school. Given their novelty, learning factories have not yet been studied with respect to whether special classroom management may be needed. One key aspect of classroom management for teachers is the dealing with classroom disruptions. The aim of this study is to investigate what types of classroom disruptions occur in learning factories and how teachers deal with them. Methods: To close the existing research gap, a guideline-based, semi-structured interview study with seven teachers from the federal state of Baden-Württemberg, Germany, was conducted. The interviews were analyzed with a qualitative content analysis using the software MAXQDA. Findings: The findings show that in this new setting, established strategies for mitigating classroom disruptions can be adapted and applied. Teachers were found to use and optimize their existing abilities to ensure learning success and were able to protect the monetary value of the factory against certain disruptions. Mutual trust between teachers and students, as well as teachers utilizing strategies according to their personality, were mentioned as the most important factors in ensuring success in this context. Conclusion: Learning factories as a new learning environment in vocational schools do not seem to require specific classroom management approaches. As a result, their use can be safely expanded. Teachers value the possibility of teaching in this special setting while seeing that there are new possible ways of disruptions. Nevertheless, the interviewees feel themselves prepared for these new challenges, using their already established repertoire of strategies, adapting them, if necessary, to this new setting. To do this, teachers need to systemize and understand disruptions inside their classrooms. So far, research is lacking systemizations for classroom disruptions in digital settings like learning factories. This study extends the research landscape with an adaption of an already existing construct.